2019
DOI: 10.20527/es.v15i1.6327
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Tinggi Muka Air Tanah Pada Lahan Gambut Yang Terbakar

Abstract: Seasonal fluctuations of water table depth are very important regarding the sustainable peat management on tropical peatland. Water level depth can affect the greenhouse gases emissions and as the main indicator for peat fire risk management. Therefore, direct measurement of water level dynamics in the peat burning area is absolutely necessary. The research objective was studied the water level fluctuations on burning peatland in Central Kalimantan, Indonesia. Water level measurement performed manually in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Furthermore, the groundwater level formed the dome shape (Figure 3). These findings confirmed the previous studies by Aswandi, Sadono, Supriyo, and Hartono (2016) and (Wakhid, Nurzakiah, and Zainudin, 2019) which reported a similar phenomenon. It has been suggested that the phenomenon seems due to water nature, which flows to a -197,4 -191,4 -178,6 -152,8 -196 Typically, groundwater level should be maintained on below the roots zone, in order to provide adequate water content and air, by controlling water level in tertiary channels (Wangsadipura, 2005).…”
Section: Introductionsupporting
confidence: 93%
“…Furthermore, the groundwater level formed the dome shape (Figure 3). These findings confirmed the previous studies by Aswandi, Sadono, Supriyo, and Hartono (2016) and (Wakhid, Nurzakiah, and Zainudin, 2019) which reported a similar phenomenon. It has been suggested that the phenomenon seems due to water nature, which flows to a -197,4 -191,4 -178,6 -152,8 -196 Typically, groundwater level should be maintained on below the roots zone, in order to provide adequate water content and air, by controlling water level in tertiary channels (Wangsadipura, 2005).…”
Section: Introductionsupporting
confidence: 93%
“…Hasil penelitian ini sama dengan hasil penelitian yang dilakukan oleh Wakhid et al (2019) yang melaporkan bahwa tinggi muka air di lahan gambut dekat saluran lebih dalam dibanding tinggi muka air lahan yang jauh dari saluran. Tinggi muka air tanah pada gambut ditentukan jarak titik pengamatan dari saluran drainase (Adji et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Tinggi muka air tanah pada gambut ditentukan jarak titik pengamatan dari saluran drainase (Adji et al, 2019). Wakhid et al (2019) mengemukakan bahwa hal ini terjadi karena sifat air yang selalu mengalir ke tempat yang lebih rendah. Hasil penelitian ini mengindikasikan perlunya pengaturan dalam pembuatan saluran di lahan gambut untuk menjaga penurunan tinggi muka air di lahan gambut yang drastis.…”
Section: Hasil Dan Pembahasanunclassified
“…Walaupun musim kemarau pada tahun 2014 lebih panjang dibandingkan musim kemarau tahun 2015, tetapi TMA terendah tetap terjadi pada tahun 2015 (Itoh et al, 2017). Dibandingkan dengan TMA yang terukur tahun 2014 pada lahan gambut yang terbakar sekitar 1 km dari plot penelitian, selisih TMA terdalam mencapai 36 cm, dimana TMA terdalam di lahan tersebut hanya -135 cm, dengan rata-rata -83 cm (Wakhid et al, 2016). Begitu juga dengan TMA tahun 2014 di hutan yang telah didrainase di Palangkaraya, selisih terdalam TMA sekitar 32 cm, dengan rata-rata TMA -55 cm (Itoh et al, 2017).…”
Section: Tinggi Muka Airunclassified